Euro area banking sector integration: using hierarchical cluster analysis techniques - Christoffer Kok Sørensen; Josep Maria Puigvert Gutiérrez (European Central Bank (ECB), 2006)
In this study we apply cluster analysis techniques, including a novel smoothing method, to detect some basic patterns and trends in the euro area banking sector in terms of the degree of homogeneity of countries. We find that in the period 1998-2004 the banking sectors in the euro area countries seem to have become somewhat more homogeneous, although the results are not unequivocal and considerable differences remain, leaving scope for further integration. In terms of clustering, the Western and Central European countries (like Germany, France, Belgium, and to some extent also the Netherlands, Austria and Italy) tend to cluster together, while Spain and Portugal and more recently also Greece usually are in the same distinct cluster. Ireland and Finland form separate clusters, but overall tend to be closer to the Western and Central European cluster.
Keywords: C49; F36; G21; 330; banking sector; cluster analysis; financial integration; Finanzsektor; Bank; Integration; EU-Binnenmarkt; Clusteranalyse; EU-Staaten